2022
DOI: 10.1590/0103-1104202213309i
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus macro-regional inequalities in PHC: comparing the three PMAQ-AB cycles

Abstract: This study aimed to identify macro-regional structure and work process inequalities for Diabetes Mellitus (DM) treatment in Primary Health Care (PHC) throughout the three cycles of the National Program for Access and Quality Improvement of Primary Care (PMAQ-AB) in Brazil. This ecological, longitudinal, nationwide study employed secondary data from the three PMAQ-AB cycles. The data were compared between the Brazilian macro-regions using the t-test with Bonferroni correction. The North and Northeast had the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…A maioria dos estudos avaliativos está focada especificamente na linha de cuidados da saúde mental (8)(9)(10)(11)(12) . Outros estudos avaliativos foram conduzidos na perspectiva da APS erevelaram suas responsabilidades como coordenadora e ordenadora do cuidado, integração com os demais pontos das RAS e o envolvimento das equipes apoiadora e de referência (10,(13)(14)(15) .…”
Section: Introductionunclassified
“…A maioria dos estudos avaliativos está focada especificamente na linha de cuidados da saúde mental (8)(9)(10)(11)(12) . Outros estudos avaliativos foram conduzidos na perspectiva da APS erevelaram suas responsabilidades como coordenadora e ordenadora do cuidado, integração com os demais pontos das RAS e o envolvimento das equipes apoiadora e de referência (10,(13)(14)(15) .…”
Section: Introductionunclassified
“…Most evaluative studies are specifically focused on the mental health care line (8)(9)(10)(11)(12) . Other evaluative studies from the APS perspective were conducted and revealed responsibilities in the coordination and ordering of care, integration with other points of health care networks (RAS) and the involvement of support and reference team (10,(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%